Development Of Piezoelectric Energy Harvesting Floor - Nur Hidayah Binti Ismail (2023)
Rapid technology and manufacturing developments have triggered an increase in energy demand globally for many years. This would require the spending of more fossil fuel and the release of more pollution. This issue has allowed many parties to look at the importance of sustainable development in the generation of energy. A number of approaches to this issue have been taken, one being the introduction of piezoelectric harvesting floor. This type of material can transform mechanical power into electrical energy directly, which can then be subsequently collected using the technology or circuit for energy harvesting. The transformation of energy from ambient vibration today is indeed an intriguing field of studies. Because of the ability to incorporate high voltage and standalone helping electromechanical and microsystems for small energy usage devices such as wireless and sensors, it is the most common electromechanical transducer material. This paper deals with how to extract energy from piezoelectric materials which are stored for later supply of electronic and electrical equipment in energy storages such as the battery. In attempt to verify the accuracy of energy extraction prototype, a simulation in MATLAB Simulink and PROTEUS is also presented and experimental data are performed out. This project can therefore be practical for the supply of energy to low-powered devices. IV